2007
DOI: 10.1021/ac061349t
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Polymerization for Entrapping of Octadecylsilane Microsphere Columns for Capillary Electrochromatography

Abstract: A novel fritless capillary column for capillary electrochromatography (CEC) has been developed. The ODS microspheres were packed into a capillary and were then immobilized within an organic polymer prepared in situ through a photopolymerization process. The entrapment conditions were investigated to minimize the effect of the polymer matrix on the chromatographic properties of the packing material. The organic polymer matrix in the microsphere-packed column functions to link microspheres at specific sphere-sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Peptides were redissolved in 5% ACN/1% formic acid and loaded onto an in-house packed polymer-fritted (24,25) trap column at 2.5 l/min (1.5 cm length, 100 m inner diameter, ReproSil, C 18 AQ 5 m 200 Å pore (Dr. Maisch)) vented to waste via a micro-tee. The peptides were eluted by split-flow at ϳ800 -1000 psi head pressure from the trap and across a fritless analytical resolving column (18 cm length, 100 m inner diameter, ReproSil, C 18 AQ 3 m 200 Å pore) pulled in-house (Sutter P-2000, Sutter Instruments, San Francisco, CA) with a 50 min gradient of 5-30% LC-MS buffer B (LC-MS buffer A: 0.0625% formic acid, 3% ACN; LC-MS buffer B: 0.0625% formic acid, 95% ACN).…”
Section: Lc-ms/ms Analysis-lc-ms/msmentioning
confidence: 99%
“…Peptides were redissolved in 5% ACN/1% formic acid and loaded onto an in-house packed polymer-fritted (24,25) trap column at 2.5 l/min (1.5 cm length, 100 m inner diameter, ReproSil, C 18 AQ 5 m 200 Å pore (Dr. Maisch)) vented to waste via a micro-tee. The peptides were eluted by split-flow at ϳ800 -1000 psi head pressure from the trap and across a fritless analytical resolving column (18 cm length, 100 m inner diameter, ReproSil, C 18 AQ 3 m 200 Å pore) pulled in-house (Sutter P-2000, Sutter Instruments, San Francisco, CA) with a 50 min gradient of 5-30% LC-MS buffer B (LC-MS buffer A: 0.0625% formic acid, 3% ACN; LC-MS buffer B: 0.0625% formic acid, 95% ACN).…”
Section: Lc-ms/ms Analysis-lc-ms/msmentioning
confidence: 99%
“…[9] Among the employed organosilanes, octadecyltrimethoxysilane (ODS) and octadecyltrichlorosilane (OTS) have been largely used for surface chemical modification. Examples of applications of these hybrid materials in the development of self-assembled monolayers (SAMS), [10] mesoporous materiais, [11] nanocomposites, [12] pharmaceutical carriers [13] and columns for electrochromatography [14][15] are found in the literature.…”
mentioning
confidence: 99%
“…One contribution to the asymmetrical bands for the previous frits was probably attributed to the adsorption of the hydrocarbon analytes on the prepared frit. 24 In our experiments, a satisfying symmetry factor was obtained in the range of 0.9-1.1 for four model analytes, respectively. Good results in our experiments showed that the novel frit was stable and practical, which offered an alternative to the traditional methods for the frit preparation.…”
Section: Reproducibility and Peak Broadeningmentioning
confidence: 53%